Race, Beauty and Resistance: A Historical Perspective (Bon Voyage, 2019)
This article surveys of the various forms of racism and their impact upon the notion of beauty in the US. After the abolition of the slavery and racially segregated legal provisions, the African- American people suffer from various forms of racial discriminations. Such racist attitudes based on Whiteman supremacy also shape the discourse and standard of women’s beauty in the US. The biological features of the white women are considered as standard of beauty and the black women are stereotyped in terms of their beauty. As a result, the black women suffer emotionally and socially, and feel pressure of changing their biological features to confirm and accommodate with the whites’ notion of beauty. However, some black women gradually resist such racist notion of beauty by exploring their cultural root and proposing a counter discourse of beauty.